Healthcare Providers' Experiences With a Clinical Mentorship Intervention to Improve Reproductive, Maternal and Newborn Care in Mwanza, Tanzania - Isangula, Kahabi; Mbekenga, Columba; Mwansisya, Tumbwene; Mwasha, Loveluck; Kisaka, Lucy; Selestine, Edna; Siso, David; Rutachunzibwa, Thomas; Mrema, Secilia; Pallangyo, Eunice (Frontiers in Health Services, 2022)
INTRODUCTION: There is increasing evidence suggesting that clinical mentorship involving on-the-job training is one of the critical resources –friendly entry points for strengthening the knowledge and skills of healthcare providers (HCPs), which in turn facilitate the delivery of effective reproductive, maternal and newborn (RMNH) care. The paper explores the experiences of HCPs following participation in the CM program for RMNH in eight districts of Mwanza Region in Tanzania. MATERIALS AND METHODS: A qualitative descriptive design employing data from midterm project review meeting and Key Informant Interviews with purposefully selected HCPs (mentors and mentees) and District Medical Officers during the endline evaluation, were employed. Interview data were managed using Nvivo Software and analysed thematically. RESULTS: About 42 HCPs responded to a questionnaire during the midterm review meeting. Then, a total of 17 KIIs was conducted with Mentees (8), Mentors (5) and DMOs (4) during endline evaluation. Five key themes emerged from participants’ accounts: (i) topics covered during CM visits; (ii) benefits of CM; (iii) challenges of CM; (iv) drivers of CM sustainability and; (iv) suggestions for CM improvement. Topics of CM covered during visits included: antenatal care, neonatal resuscitation, pregnancy monitoring, management of delivery complications and, infection control and prevention. Benefits of CM included: increased knowledge, skills, confidence and change in HCPs attitude and, increased client service uptake, quality and efficiency. Challenges of CM included: inadequate equipment for self-learning and practice, the limited financial incentive to mentees, shortage of staff, time constraints and, weaker support from management. Drivers of CM sustainability included: willingness of mentees to continue with clinical practice, ongoing peer-to-peer mentorship and, integration of the mentorship program into district health plans. Finally, suggestions for CM improvement included: refresher trainings for mentors, engagement of more senior mentors and extending mentorship beyond IMPACT catchment facilities. CONCLUSION: CM program appears to be a promising entry point to improving competence among HCPs and quality and efficiency of RMNH services potentially contributing to the reduction of maternal and neonatal deaths. Addressing the challenges cited by participants, particularly the equipment for peer learning and practice, may increase the success of CM program.